2020
DOI: 10.1194/jlr.ra119000455
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue lipoprotein and glucose disposal is not determined by thermogenesis in uncoupling protein 1-deficient mice

Abstract: Adaptive thermogenesis is highly dependent on uncoupling protein 1 (UCP1), a protein expressed by thermogenic adipocytes present in brown and white adipose tissues (BAT, WAT). Thermogenic capacity of human and mouse BAT can be measured by positron emission tomography-computed tomography (PET-CT) quantifying the uptake of 18F-fluodeoxyglucose or lipid tracers. BAT activation is typically studied in response to cold exposure or treatment with beta-3-adrenergic receptor agonists such as CL316,243. Currently, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 97 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…Fatty acid β-oxidation fuels the increase in uncoupled mitochondrial respiration and contributes to inducing the expression of thermogenic genes such as UCP1 [ 71 ]. UCP1 is a hallmark of brown adipocytes and plays a pivotal role in BAT thermogenic function since it confers to brown adipocytes their specific ability to dissipate the proton gradient as heat, and its downregulation or absence has been reported to be associated with impaired BAT thermogenic capacity and lower EE [ 72 , 73 , 74 ]. The efficacy of melatonin to induce UCP1 expression in iBAT has already been demonstrated by other groups in experimental ageing and melatonin deficient models, and the melatonin doses offered to animals have ranged from 1 to 10 mg/kg.bw [ 64 , 65 , 66 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid β-oxidation fuels the increase in uncoupled mitochondrial respiration and contributes to inducing the expression of thermogenic genes such as UCP1 [ 71 ]. UCP1 is a hallmark of brown adipocytes and plays a pivotal role in BAT thermogenic function since it confers to brown adipocytes their specific ability to dissipate the proton gradient as heat, and its downregulation or absence has been reported to be associated with impaired BAT thermogenic capacity and lower EE [ 72 , 73 , 74 ]. The efficacy of melatonin to induce UCP1 expression in iBAT has already been demonstrated by other groups in experimental ageing and melatonin deficient models, and the melatonin doses offered to animals have ranged from 1 to 10 mg/kg.bw [ 64 , 65 , 66 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since UCP1 in BAT is inactive at thermoneutrality, the lack of thermogenic BAT function should be without consequences for energy balance. Indeed, several studies using the established UCP1-KO mouse model originally generated by Leslie Kozak and coworkers confirmed this expectation (Enerbäck et al 1997; Liu et al 2003; Zietak and Kozak 2016; Winn et al 2017; Maurer et al 2020; Fischer et al 2020). In contrast, other studies reported that UCP1 knockout mice are more susceptible to diet induced obesity at thermoneutrality (Feldmann et al 2009; von Essen et al 2017; Rowland et al 2016; Luijten et al 2019; Pahlavani et al 2019).…”
Section: Introductionmentioning
confidence: 87%
“…ProDy & DynOmics can be used for glycoprotein modeling. 88 A general purpose of these computational tools is to detect glycosylation terminal regions in deglacosylated proteins and to obtain more correct information about N-and O-linked glycoproteins.…”
Section: Wang Et Al Compared Systematically Glycoprotein Migration On...mentioning
confidence: 99%
“…For instance, GlycoSeq, GlypID, and GlycoPep Evaluator (GPE) were developed for identifying glycopeptide structures in antibodies. ProDy & DynOmics can be used for glycoprotein modeling 88 . A general purpose of these computational tools is to detect glycosylation terminal regions in deglacosylated proteins and to obtain more correct information about N ‐ and O ‐linked glycoproteins.…”
Section: Experimental Toolsmentioning
confidence: 99%